Mechanical Properties Of Bamboo Particle Reinforced Polylactic Acid (Pla) Composite Using Taguchi Method - Mohd Johary, Nurnadia (2021)
This thesis discusses the manufacturing of composites made from PLA and bamboo particles using extrusion and compression moulding techniques. In order to explore the potential of the composites, a study of physical, thermal, mechanical and morphological properties was examined. This research focuses on improving the mechanical properties of PLA-bamboo of PLA-bamboo particle composite by optimising the parameters that influence the properties using Taguchi experimental design.